(untitled) (Research, Society and Development, 2020)
The aim of this study was to analyze prevalence of tuberculosis among inmates at the Regional Prison in Feira de Santana-BA and preventive and follow-up measures adopted to disease’s control. This is a retrospective, field research with a quantitative and qualitative approach developed in two stages: the first stage was carried out through epidemiological data collection related to prevalence of tuberculosis in the prison population available at the Health Department of the Municipality of Feira de Santana (BA); the second stage was developed through a semi-structured interview with the nursing coordination of Penal Settlement of Feira de Santana-BA. It was observed that among the 130 confirmed cases of tuberculosis in prisioners, 99.23% were men and 0.77% were women and a maximum prevalence of 27.6 cases of tuberculosis per 1,000 inhabitants was observed throughout the study period. This study may be relevant to assume that the problem of tuberculosis among detainees goes further. Health and safety issues are really important but not investing in effective actions to avoid disease in the prison environment puts at risk the effectiveness of other measures implemented for its control, thus perpetuating tuberculosis as a serious public health problem.